Osobennosti projavlenija mikroparoksizma u junych sportsmenov-lyžnikov v processe sportivnoj podgotovki - Korelskaya, I. E.; Sharenkova, L. A.; Zelyanina, A. N. (Theory and Practice of Physical Culture, 2018)
The study considers the most topical and problematic issues of the junior cross-country skiers` training process with a special focus on their exposure to micro-paroxysms triggered by high physical and mental stressors. Sampled for the study were the 13-15 cross-country skiers trained in the Far North of Europe. The sample`s exposure to micro-paroxysms was rated by the sensorimotor response level and stability tests, with the responses triggered by light impulses; and with the tests designed in a standard simple visual motor response rating format. The study data made it possible to identify the age- and personality-specific variations in the individual exposure to micro-paroxysms; and analyze the micro-paroxysm occurrence statistics on a differentiated basis. The marginal conditions were rated within the range of 0 to 14 points, with the scores on the 14-point scale being indicative of the high competitive fitness or reluctance to compete. The study failed to find significant correlations between the simple sensorimotor response rates and exposure to micro-paroxysms. Therefore, the exposure to micro-paroxysms may be considered largely age-specific and, to a degree, associated with the high motivations for success in the cross-country skiing sport.